Respuesta :

Answer:

From the given strategies , we can choose option B for eliminating variables .

Step-by-step explanation:

Given as :

The two linear equation

2 x - 5 y = 13              .......A

- 3 x + 2 y = 13           .......B

Now, According to question

A ) Subtract bottom equation from top equation

(- 3 x + 2 y) - (2 x - 5 y) = 13 - 13

Or, (- 3 x - 2 x) + (2 y + 5 y) = 0

Or, - x + 7 y = 0

So, From calculation we get that variables are not eliminated

Again

B) Multiply the top equation by 3 , multiply the bottom equation by 2, then add the equation

3 × (2 x - 5 y) + 2 × ( - 3 x + 2 y) = 3 × 13 + 2 × 13

Or, 6 x - 15 y - 6 x + 4 y = 39 + 26

Or, (6 x - 6 x) + (- 15 y + 4 y) = 65

Or, 0 - 11 y = 65

∴  y = [tex]\frac{65}{- 11}[/tex]

Put the value of y in eq A

∵ 2 x - 5 y = 13  

Or, 2 x = 13 + 5 y

Or, 2 x = 13 + 5 ( [tex]\frac{65}{- 11}[/tex])

Or, x = [tex]\frac{-91}{11}[/tex]

So, while applying this condition we can eliminate variables

Again

C) Multiply the top equation by 2 , multiply the bottom equation by 3, then add the equation

2 × (2 x - 5 y) + 3 × ( - 3 x + 2 y) = 2 × 13 + 3 × 13

Or, 4 x - 10 y - 9 x + 6 y = 26 + 39

Or, (4 x - 9 x) + (- 10 y + 6 y) = 65

Or,  - 13 x - 4 y = 65

So, while applying this condition we can not eliminate variable

Hence, From the given strategies , we can choose option B for eliminating variables . Answer

ACCESS MORE